A Survey of Factors That May Cause Practice Inconsistencies and Impact Care in Pulmonary Rehabilitation. Issue 1 (January 2022) - Pata, Rachel W.; Giblin, Jillian; Cassata, Emily; Cortez, Regina; Pascale, Alicia; Hall, Megan
Abstract : Purpose: Research about methods implemented in pulmonary rehabilitation is needed. Inconsistencies in this multifaceted intervention may impact care. Methods: A survey was administered to outpatient pulmonary rehabilitation programs, addressing program characteristics, and perceived importance and frequency of rehabilitation components. Descriptive statistics and post-hoc correlations were analyzed. Results: Clinicians present during exercise included respiratory therapists (72.2%), exercise physiologists (50%), registered nurses (44.4%), physical therapists (11.1%), occupational therapists (5.6%), dieticians (5.6%), and physicians (5.6%). On a scale of 1 to 5 (never vs always), programs provided: exercises for all extremities (5), individualized exercise (4.89, SD = 0.46), resistance training (4.5, SD = 0.83), balance training (3.28, SD = 1.1), alternative exercise methods (1.94, SD = 1.55), home equipment education (3.44, SD = 1.12), social support avenues (3.83, SD = 1.26), and home safety assessments (1.56, SDs = 1.07). All programs offered warm-up, cool down, and breathing exercises; 44% offered inspiratory resistance training, 22% high-intensity aerobic, and 11% high-intensity interval training. Twenty-four varied resources were used for patient education. Smoking cessation and nutritional consults were inconsistently offered. Reported limiting factors included compliance (66.7%), transportation (55.6%), staffing (33.3%), and facility size (33.3%). Conclusions: Limited resources, varied personnel, and patient compliance may contribute to practice inconsistencies. Improved resources, transportation, and an inclusive team may improve care standardization. Abstract : Supplemental Digital Content is Available in the Text.